Review on the epidemiology of Bovine Rotavirus and its public health significance - Abebe Garoma Gichile (International Journal of Veterinary Science and Research - Peertechz Publications, 2022)
A literature review was made to assess the epidemiology, public health importance, diagnostic and control methods of bovine rotavirus. Rotavirus is the genus name under the family Reoviridae which is characterized by segmented genome. The emergence of new serotypes of the virus is related to the segmented nature of the viral genome which allows reassortment during mixed infections. The rotavirus genome consists of 11 double-stranded RNA gene segments encoding 6 nonstructural (NSP1-6) and 6 structural (VP1-4, VP6-VP7) proteins. Rotavirus A is a zoonotic disease and in children less than five years old, human rotavirus is reported to be the most common cause of gastritis. In animals, rotavirus infection usually affects calves within four weeks of age, causing huge economic losses due to death, reduction in weight gain and treatment costs. Bovine rotaviruses are globally distributed and cattle strains have been classified into 12 G types and 11 P types and among them G6, G8 and G10, and P [1], P [5] and P [11] are commonly prevalent bovine strains. However, the presence of 14 G type and 17 P type serotypes from human have reported in different surveillance studies worldwide. Among these, combinations of G1P [8], G2P [4], G3P [8], G4P [8], G9P [8] and G12P [8] are the most common human strains which are responsible for majority of human Rotavirus diseases. The virus is primarily transmitted by fecal-oral route or by direct contact. The excreta from infected animals and humans, excreta contaminated food; water, pasture and air are the potential source of infection for both animal and human rotaviruses. Age, seasonal pattern, strain diversity, poor herd management and housing system, host nutritional and immunological factors are important risk factors associated with rotavirus disease occurrences. The widely used diagnostic methods for detection of rotavirus antibody in human and animals are Enzyme-Linked Immunosorbent Assay (ELISA) and immune-chromatography while the presence of the rotavirus/antigen is identified by Enzyme Immunoassay (EIA). Electron Microscopy (EM), polymerase chain reaction (PCR) and nucleic acid hybridization. Vaccination is the primary strategy to prevent and control of bovine and human rotavirus infections. High level of antibody in pregnant animals is achieved through live attenuated and inactivated vaccines when administered at the late stage of pregnancy. In human, the two currently used vaccines are the RV5 vaccine (USA) and the RV1 vaccine (Belgium) types.